2015
DOI: 10.1002/marc.201500356
|View full text |Cite
|
Sign up to set email alerts
|

Toward Hybrid Materials: Group Transfer Polymerization of 3‐(Trimethoxysilyl)propyl Methacrylate

Abstract: In this study, the group transfer polymerization (GTP) of the functional monomer 3‐(trimethoxysilyl)propyl methacrylate (TMSPMA) is reported to produce polymers of different architectures and topologies. TMSPMA is successfully polymerized and copoly­merized with GTP to produce well‐defined (co)polymers that can be used to fabricate functional hybrid materials like hydrogels and films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…He et al prepared tadpole-shaped "silica-like" nanoparticles with ap olymer tether by self-collapse/sol-gel reaction of the TMSPMA containing block in single polymer chains of TMSPMA-containing block copolymers. [27,43] For PEO 114 -b-P(TMSPMA 32-124 -r-MMA 55-423 )t adpole-shaped "silica-like" nanoparticles with PEO tether wereo btained, [43] while for PS 205 -b-P(tBA 45-352 -co-TMSPMA 4-56 )a nd PS 99 -b-P(tBA 64,106 -co-TMSPMA 23,24 )-b-PS 99 one or two PS tethers were obtainedo n the NPs, respectively. [27] The preparation of such tadpoleshaped nanoparticles was carried out in ad ilute copolymer THF solution in the presence of ammonium hydroxide as base.…”
Section: Pickeringemulsifiersmentioning
confidence: 99%
See 2 more Smart Citations
“…He et al prepared tadpole-shaped "silica-like" nanoparticles with ap olymer tether by self-collapse/sol-gel reaction of the TMSPMA containing block in single polymer chains of TMSPMA-containing block copolymers. [27,43] For PEO 114 -b-P(TMSPMA 32-124 -r-MMA 55-423 )t adpole-shaped "silica-like" nanoparticles with PEO tether wereo btained, [43] while for PS 205 -b-P(tBA 45-352 -co-TMSPMA 4-56 )a nd PS 99 -b-P(tBA 64,106 -co-TMSPMA 23,24 )-b-PS 99 one or two PS tethers were obtainedo n the NPs, respectively. [27] The preparation of such tadpoleshaped nanoparticles was carried out in ad ilute copolymer THF solution in the presence of ammonium hydroxide as base.…”
Section: Pickeringemulsifiersmentioning
confidence: 99%
“…[22] The block copolymers wereo btainede ither by ao ne pot procedure or in a two-stepr eaction by first isolating PMMA and using it as macroinitiator.M ore recently,G eorgiou et al prepared TMSPMA and MMA based linear diblock copolymers in ao ne-pot synthesis, via GTP in THF at 20 8Cu sing 1-methoxy-1-(trimethylsiloxy)-2-methyl propene (MTS) as initiator.T hey obtained copolymers with low degree of polymerization (DP % 20 fore ach block)a nd low dispersity of 1.05, as can be expected from this polymerization method. [23] Finally,G ao et al reported the synthesis of PMMA-b-PTMSPMA copolymers of higherm olar mass (M n % 39 kDa) from either ethyl 2-bromoisobutyrate (EBiB) or a fluorinated initiator by two sequential CuCl/PMDETAm ediated ATRP in cyclohexanone: first MMA was polymerizeda t9 0 8C, followed by TMSPMA at 110 8C. [24] Fukuda.…”
Section: Substituentsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of MPTS interaction with TEOS, they form cured particles containing the unsaturated double bonds of MPTS on the surface [22]. The preparation of the linear poly(MPTS) and block-copolymers poly(MPTS)-block-poly(MMA) that were further used for obtaining cured and star-like polymers was described [35]. Porous coatings were obtained using blockcopolymers poly(styrene)-block-poly(MPTS), as shown in [36].…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of the linear poly(MPTS) and block-copolymers poly(MPTS)-block-poly(MMA) that were further used for obtaining cured and star-like polymers was described [35]. Porous coatings were obtained using blockcopolymers poly(styrene)-block-poly(MPTS), as shown in [36]. As a result of MPTS radical polymerization initiated by the AIBN, poly(MPTS) was synthesized, then cured polymer was obtained in water-alkaline solution in the presence of acid as a promoter of the polycondensation [37].…”
Section: Introductionmentioning
confidence: 99%